Defending Women Beyond Feminism: Gender Perspectives in Indonesia - Nur Mutiullah, Muhammad Yaufi (Jurnal Theologia, 2024)
This article examines the development of gender understanding in Indonesia. Specifically, the understanding of gender discussed in this article comes from the perspective of one of the leading Islamic organizations in Indonesia, namely Nahdlatul Ulama (NU), which has its own way of thinking in defending women's rights. This article aims to show that Nahdlatul Ulama's concept of defending women is different from the concept of feminism that emerged in Western civilization, namely by looking at the capabilities and capabilities of women themselves. Therefore, I use the words "Defending Women But Not Feminism" with the intention of emphasizing that the way NU defends women's rights is not based on the feminist paradigm way of thinking that has developed in modern times. The research methodology used in this research is a qualitative approach. This article uses library research procedures, especially analytical descriptive methods. This research uses book data, relevant literature, and other important sources. This research uses document analysis as a qualitative research methodology. The results of this research show that NU's thinking paradigm in defending women's rights is different from Western feminism. NU has a different view in defending women's rights, namely "beyond feminism”.